Kemampuan Koneksi Matematis Siswa SMA Berdasarkan Kecemasan Matematika - Astuti, Juwita; Caswita, Caswita (Media Pendidikan Matematika, 2021)
One of mathematical abilities which is concepted by NTCM must be mastered by a student is mathematical connections. Some Studyâ€™s results showed that mathematics anxiety can influence students’ mathematical abilities, including mathematical connections abilities. The study intends to know aboutÂ mathematical connectionâ€™s ability that will be reviewed from high school students,s mathematics anxietyÂ in solving problem related to material sequences and series. The samples in this study were 36 students of class XI IPA 2 at SMA N 1 Sekampung Â in East Lampung in Â academic year 2020/2021. Qualitative approach with descriptive method is used in this study. The tehnicque in collecting the data in this study byÂ providing students math anxiety quessionair and Â tests to see the abilities of mathematical connections. There were 8 students indicated high math anxiety, 19 students indicated moderate math anxiety and 9 students indicated low math anxiety. The analysis was focused onÂ the students who are chosen as the subject from each category. The conclusion is that student indicated Â high mathematics anxiety was able to achieve the ability to connect mathematical topics, connect mathematical topics to other sciences, while students with moderate and low mathematics anxiety can only achieve mathematics connection ability in indicator of connection in and between mathematical concepts. There is an anomaly in this study, which is due to high mathematics anxiety student getÂ mathematical connection ability tend to be better. Keywords : Mathematical connection, mathematics anxiety, sequence